Dari Etika ke Ekologi: Interpretasi Ekonomi Hijau dan Biru dalam Pemikiran M. Umer Chapra sebagai Imajinasi Baru Ekonomi Berkelanjutan - Mahdiah Mumtaza Husna; Atmo Prawiro (Yayasan Literasi Sains Indonesia, 2026)
This article examines the relevance of M. Umer Chapra’s thought in constructing a just green economy and blue economy as a response to the climate crisis, terrestrial - marine ecosystem degradation, and increasing social inequality. This topic is significant because mainstream green - blue economy approaches remain largely technocratic and insufficiently integrated with ethical and institutional dimensions. The main research problem addresses how Chapra’s ethical - institutional framework can enrich and guide the green - blue economy agenda toward greater justice, sustainability, and long-term welfare orientation. The novelty of this study lies in its systematic effort to bridge Chapra’s thought with green and blue economy frameworks through the formulation of an integrative conceptual model linking values, policies, institutions, and implementation instruments. This study employs a qualitative-analytical approach using a comparative case study design based on library research and content analysis. Data are derived from Chapra’s seminal works, international policy documents (SDGs, UNEP, OECD, World Bank), expert interviews, and contemporary literature from the period 2020 - 2025. The findings reveal a strong correspondence between Chapra’s core values (amanah, maslahah, and justice) and the principles of the green - blue economy, particularly in resource management, governance, distributive justice, and the prevention of negative externalities. The study concludes that integrating Chapra’s thought produces an ethical - institutional framework that enhances the legitimacy, effectiveness, and sustainability of the green - blue economy transition, while providing a roadmap for inclusive, just, and ecologically resilient economic development.